2016
DOI: 10.1074/jbc.m115.712414
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the Yeast Mitochondrial Iron-Sulfur Cluster Assembly Machinery

Abstract: The biosynthesis of Fe-S clusters is a vital process involving the delivery of elemental iron and sulfur to scaffold proteins via molecular interactions that are still poorly defined. Furthermore, molecular modeling suggests that two subunits of the cysteine desulfurase, Nfs1, may bind symmetrically on top of two adjacent Isu1 trimers in a manner that creates two putative [2Fe-2S] cluster assembly centers. In each center, conserved amino acids known to be involved in sulfur and iron donation by Nfs1 and Yfh1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 65 publications
(145 reference statements)
6
28
0
Order By: Relevance
“…We found that overexpression of YFH1 results in increased Yfh1 in mitochondria, yet it only showed mild suppression of the sterol intermediate accumulation seen in ⌬erg29 cells. It may be that oxidized Yfh1 is functionally inactive or that Yfh1 suppresses the ⌬erg29 phenotype by chelating iron, as Yfh1 has been suggested to be an iron-binding protein (8,11,50). The function of Pet20 is unclear except that its loss renders respiratory active yeast susceptible to a wide variety of conditions, including H 2 O 2 and the antifungal drug fluconazole (15).…”
Section: Increased Sterol Intermediates Affect Fe-s Cluster Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…We found that overexpression of YFH1 results in increased Yfh1 in mitochondria, yet it only showed mild suppression of the sterol intermediate accumulation seen in ⌬erg29 cells. It may be that oxidized Yfh1 is functionally inactive or that Yfh1 suppresses the ⌬erg29 phenotype by chelating iron, as Yfh1 has been suggested to be an iron-binding protein (8,11,50). The function of Pet20 is unclear except that its loss renders respiratory active yeast susceptible to a wide variety of conditions, including H 2 O 2 and the antifungal drug fluconazole (15).…”
Section: Increased Sterol Intermediates Affect Fe-s Cluster Synthesismentioning
confidence: 99%
“…Many of the genes involved in Fe-S cluster synthesis and particularly in the mitochondrial synthesis and export of Fe-S clusters are highly conserved in all eukaryotes. Yfh1, the yeast equivalent of mammalian frataxin, plays an important role in the early steps of Fe-S cluster synthesis (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Whereas the exact role has not been defined, loss of Yfh1 results in severely compromised Fe-S cluster synthesis and decreased mitochondrial function.…”
mentioning
confidence: 99%
“…Frataxin, which was shown to interact with the preformed ternary complex 55 , was proposed to bind in a ratio of 1:2:1:1 in the quaternary complex (NFS1:ISD11:ISCU:FXN) 54 . The source of iron for the nascent cluster remains to be identified, but proposed donors include frataxin 56, 57 , which has acidic surface patches to which iron binds with low affinity, or a complex of glutathione and glutaredoxin 58 . Electrons, needed to achieve the final electronic configurations of Fe-S clusters, are provided by ferredoxins (FDX1/2) and ferredoxin reductase (FDXR) 59, 60 .…”
Section: Fe-s Cluster Biogenesis: the Assembly Stepmentioning
confidence: 99%
“…An array of techniques and methods has been developed to enable researchers to obtain intact and biologically active Fe–S proteins in pure and stable forms. In addition, methods for the generation of highly concentrated samples containing Fe-S clusters isotopically labelled with 57 Fe for Mössbauer and related spectroscopies have enabled researchers to identify novel mammalian Fe-S proteins, and to uncover new biological functions for Fe-S clusters in cellular metabolism 26 .…”
Section: Introductionmentioning
confidence: 99%
“… 24 The availability of the iron-free and functional Yfh1 Y73A and FXN 42–210 oligomers has recently enabled structural studies to characterize iron-independent protein–protein interactions involved in the yeast and human Fe–S cluster assembly machineries. 16 , 17 These macromolecular complexes share architectures suitable to ensure the concerted and protected transfer of potentially toxic iron and sulfur atoms to the scaffold during Fe–S cluster assembly. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%